In vitro and in vivo anti-salmonella properties of hydroethanolic extract of Detarium microcarpum Guill. & Perr. (Leguminosae) root bark and LC-MS-based phytochemical analysis. (5th October 2020) - Mbock, Michel Arnaud; Fouatio, William Feudjou; Kamkumo, Raceline Gounoue; Tsouh Fokou, Patrick Valère; Tsofack, Florence Ngueguim; Lunga, Paul-Keilah; Essia Ngang, Jean Justin; Boyomo, Onana; Nkengfack, Augustin Ephrem; Ndjakou, Bruno Lenta; Sewald, Norbert; Boyom, Fabrice Fekam; et al.
Abstract: Ethnopharmacological relevance: Typhoid fever treatment remains a challenge in endemic countries. Detarium microcarpum is traditionally used to manage typhoid. Aim of the study: The study aims to explore the efficacy of hydroethanolic extract of Detarium microcarpum root bark in rats infected with salmonella. Material and methods: The phytochemical profile of the extract was obtained by UHPLC-MS analysis in an attempt of standardization. The in vitro antimicrobial activity was determined using broth dilution method. Salmonella infection was induced by oral administration of S. thyphimurium to immunosuppressed rats. Infected rats were then treated 2 h later with the extract (75, 150 and 300 mg/kg), distilled water (normal and salmonella control) and ciprofloxacin (8 mg/kg) for control. Body weight was monitored and stools were cultured to determine the number of colony-forming units. At the end of treatment, animals were sacrificed, blood and organs were collected for hematological, biochemical and histopathological analyses. Results: Detarium microcarpum extract as well as the isolated compound (rhinocerotinoic acid) exhibited good antimicrobial activity in vitro with bacteriostatic effects. The plant extract significantly (p < 0.05) inhibited the bacterial development in infected animals with an effective dose (ED50 ) of 75 mg/kg. In addition, the extract prevented body weight loss, hematological, biochemical and histopathological damages in treated rats. Conclusion: Detarium microcarpum extract possesses antisalmonella properties justifying its traditional use for the typhoid fever management. Graphical abstract: Image 1